Antibiotic Resistance Crisis - og’li, Bahodirov Behruz Shavkat (American Journal of Biomedicine and Pharmacy, 2024)
Irrational Antibiotic Therapy: A Global Concern and Widespread Scourge. Prescribing antibiotics "just in case" for acute respiratory viral infections and viral diarrhea, inappropriate dosages, unsuitable medications, incorrect treatment durations, and unwarranted antibiotic combinations—these issues are compounded by low patient adherence: "took it once, forgot it twice." Rational use of any medication is a fundamental principle of clinical practice. Violating this principle leads to reduced quality of care, increased treatment costs, and a higher risk of side effects. When it comes to antibiotics, in addition to all the aforementioned consequences, improper use can exacerbate a severe global issue: the rise of antibiotic resistance in pathogenic microorganisms.